2023
DOI: 10.18060/26063
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of STEM Enrichment Programs on Wage Differentials Among Under-Represented Minority Students

Abstract: This study focuses on the increasing disparities in STEM education achievement and long-term wage earnings of under-represented minority groups. As part of national efforts to improve the diversity of the STEM workforce, this study uses longitudinal data from the University of Houston’s Education Research Center (UH-ERC) to examine the effect of participation in a STEM focused intervention program (Houston-Louis Stokes Alliance for Minority Participation) on wage earnings across students from traditionally und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, there is a precedent of successful STEM intervention programs demonstrating an increase in persistence in STEM for URM and low-income students. These programs [9], [11], [12], [13] showed that students who have participated in STEM intervention programs had a higher probability of completing STEM programs than non-participants.…”
Section: Background and Literature Reviewmentioning
confidence: 98%
“…Furthermore, there is a precedent of successful STEM intervention programs demonstrating an increase in persistence in STEM for URM and low-income students. These programs [9], [11], [12], [13] showed that students who have participated in STEM intervention programs had a higher probability of completing STEM programs than non-participants.…”
Section: Background and Literature Reviewmentioning
confidence: 98%